Perbedaan Tingkat Depresi Antara Ibu Dari Anak Gangguan Cerebral Palsy Dengan Ibu Dari Anak Gangguan Attention Deficit Hyperactivity Disorder (Adhd) Di Yayasan Pembinaan Anak Cacat (YPAC) Surakarta - Restuning Aji, Mita (2016)
Background: Depression is defined as mental disorder characterized by one depression episode or more, loss of interest on all wonderful things with concomitant symptoms such as energy deprivation, loss of appetite, hard to concentrate, guilt and discourage.The aim of this study is to determine the difference of depression rate between a mother with cerebral palsy and ADHD child in YPAC Surakarta. Methods: This study design is observational analytic with cross sectional approach. It includes 70 subjects recruited by purposive sampling technique. Data analysis is conducted in a computerized manner by using unpaired t comparison test. Results: The highest depression rate in this study belongs to the mother with cerebral palsy child. Statistical analysis using unpaired t test showed 0,001 significance value (P<0,05). Conclusion: Based on this study results, it can be concluded that there is a significance difference on depression rate between a mother with cerebral palsy and ADHD child in YPAC Surakarta (p=0,001). The mother with cerebral palsy child (11,09±4,70) is more depressed compared with the mother with ADHD child (7,11±5,16).